Membangun Website E-commerce di Toko Sean Shoes Menggunakan Metode Rapid Application Development - Dhimas Adhinar Afriansyah; Donna Setiawati; Arief Rais Bahtiar (JITU : Journal Informatic Technology And Communication, 2022)
Sean Shoes store is a store that sells women's shoes. Constraints experienced by the Sean Shoes store are frequent errors in reporting and making it difficult for the owner to obtain information in a fast and accurate time. The Sean Shoes store requires an e-commerce web-based sales facility or service that can meet the needs and can facilitate the Sean Shoes store in running its business such as sales, purchases, promotion of goods, payments and transactions. This system is designed using UML modeling built using the PHP programming language (framework codeingniter) with the Rapid Application Development system development method. the result achieved by the author is an online sales system at the web-based Sean Shoes store using the PHP programming language and using the codeingniter framework. The shoe sales system at the Sean Shoes store will make it easier for customers to make transactions and help the store promote their products. This system has been tested by testing Black Box testing and beta testing through questionnaires to website users. The results of the Black Box test show that the functions on this website system as a whole have been running well without any errors.